Phosphatidylcholine synthesis in yeast. - J Chin; K Bloch (Journal of Lipid Research, 1988)
The two pathways for the biosynthesis of phosphatidylcholine, by way of phosphocholine and by methylation of phosphatidylethanolamine, in wild-type yeast (Saccharomyces cerevisiae) and in the yeast mutant GL7 have been compared. The mutant requires for growth a sterol, unsaturated fatty acids, and methionine. The uptake of labeled choline or labeled methionine and their conversion to phosphatidylcholine were determined in both cell types. The activities of the major enzymes for both pathways were assayed in vitro. We find that the methylation pathway is predominant in both wild-type and mutant cells though the overall activity of the choline pathway is lower in the yeast mutant. The methionine analogue ethionine inhibits the growth of the mutant more strongly than growth of wild-type yeast. Ethionine, while a powerful inhibitor of phosphatidylcholine synthesis by methylation, stimulates the choline pathway in both cell types.